Comedy’s time spell - Jerónimo, Nuno Amaral (2019)
In this paper, the authors intend to reflect upon the social time interrupted by humor, as a discourse recipe, and by comedy, as a performative resource. The incongruity of the significations produced by this stylistic form means a suspension of the tipification rules in the life-world daily interactions. These moments of suspension are designated by time out. In this text, the authors show how humour and comedy connect with common time and time out to reveal interpretation keys to disclose the intersubjective social fabric.